Targeted folate-conjugated pluronic P85/poly(lactide-co-glycolide) polymersome for the oral delivery of insulin. (11th October 2018) - Xie, Shuang; Gong, Yan C; Xiong, Xiang Y; Li, Zi L; Luo, Yue Y; Li, Yu P
Aim: To explore the better efficacy of targeted folic acid (FA)-Pluronic 85-poly(lactide- co -glycolide) (FA–P85–PLGA) polymersome in oral insulin delivery.Materials & methods: The cytotoxicity of the polymers, in vitro qualitative and quantitative cellular uptake and the internalization mechanism of insulin-loaded FA–P85–PLGA and PLGA–P85–PLGA polymersomes were studied with the human colon adenocarcinoma cells (Caco-2 cells). Their pharmacodynamics and pharmacokinetics properties were also studied with diabetic rats.Results & conclusion: Polymersomes have shown good biocompatibility. Polymersomes are mainly localized within the cytoplasm of Caco-2 cells from fluorescence microscopy images. FA–P85–PLGA exhibited higher cellular uptake than PLGA–P85–PLGA polymersomes and free fluorescein isothiocyanate-labeled insulin (FITC–insulin) did. The uptake process of targeted polymersomes included clathrin- and caveolae-mediated endocytosis, macropinocytosis and the folate receptor-mediated endocytosis. Insulin-loaded FA–P85–PLGA showed better hypoglycemic effects than insulin-loaded PLGA–P85–PLGA.